Acute Effects of Low-Intensity Electrical Stimulation on Segmental Arterial Stiffness - Oda, Hiroyuki; Fujibayashi, Mami; Matsumoto, Naoyuki; Nishiwaki, Masato (Frontiers in Physiology, 2022)
Electrical muscle stimulation (EMS) has traditionally been employed to improve muscle strength and glucose uptake. EMS may also reduce arterial stiffness, but little is known about whether low-intensity EMS reduces systemic and/or regional arterial stiffness. This study aimed to examine the effects of low-intensity EMS of the lower limbs on segmental arterial stiffness. Fourteen healthy subjects participated in experiments under two different protocols (control resting trial (CT) and electrical stimulation trial (ET)) in random order on separate days. The EMS was applied to the lower limbs at 4 Hz for 20 min at an intensity corresponding to an elevation of approximately 15 beats/min in pulse rate (10.7 ± 4.7% of heart rate reserve). Arterial stiffness was assessed by cardio-ankle vascular index (CAVI), CAVI0, heart-ankle pulse wave velocity (haPWV), brachial-ankle pulse wave velocity (baPWV), heart-brachial pulse wave velocity (hbPWV), and carotid-femoral pulse wave velocity (cfPWV). In both trials, each parameter was measured at before (Pre) and 5 min (Post 1) and 30 min (Post 2) after trial. After the experiment, CT did not cause significant changes in any arterial stiffness parameters, whereas ET significantly reduced CAVI (from Pre to Post 1: -0.8 ± 0.5 unit P < 0.01), CAVI0 (from Pre to Post 1: -1.2 ± 0.8 unit P < 0.01), haPWV (from Pre to Post 1: -47 ± 35 cm/s P < 0.01), and baPWV (from Pre to Post 1: -120 ± 63 cm/s P < 0.01), but not hbPWV or cfPWV. Arm diastolic blood pressure (BP) at Post 2 was slightly but significantly increased in the CT compared to Pre or Post 1, but not in the ET. Conversely, ankle diastolic and mean BPs at Post 1 were significantly reduced compared to Pre and Post 2 in the ET (P < 0.01). These findings suggest that low-intensity EMS of the lower limbs reduces arterial stiffness, but only in sites that received EMS.